Development of Tourist Attractions in Kutri Pekraman Village - Oka Mahagangga, I GA.; Anom, I Putu (Udayana Journal of Social Sciences and Humanities; Vol 1 No 2 (2017): UJoSSH, September 2017, 2017)
This study is inspired by the existence of Bukit Darma Durga Kutri Temple located in Kutri Pekraman Village in Buruan Village, Blahbatuh Sub-regency, Gianyar Regency. Bukit Darma Durga Kutri Temple as an archaeological heritage possesses tourism potentials if it is managed holistically. This study aims to develop a strategy for the development of Kutri Pekraman Village with the tourist attractions that it has in store as a tourist village. This study employs the qualitative paradigm paired with a combination of both the qualitative and qualitative methods (mixed methods) and the SWOT analysis as the data analysis technique. The research method used is a combination of both the quantitative and qualitative methods with the qualitative paradigm as the main approach to the study. As for the sampling, qualitatively the technique used is the purposive sampling technique where there are four informants, and quantitatively the technique used is the total sampling technique where there are 100 respondents from the local residents and 15 foreign tourists. The result of the study indicates that the people of Kutri Pekraman Village in Buruan, Blahbatuh Sub-regency, Gianyar Regency are ready to carry out the development of a tourist village using all tourism potentials that are considered to be very attractive for tourists. The result of the analysis points to the strategy of future tourism development as a tourist village with the approach of alternative tourism (heritage tourism) with Bukit Darma Durga Kutri Temple as the core of the tourism, supported by the rice field areas which are popular among tourists for tracking and cycling activities.